Assessing the impact of cataract phacoemulsification at the level of intraocular pressure in patients with pseudoexfoliation syndrome (Ukrainian Journal of Ophthalmology, 2026)
Material and methods. The study was conducted on 258 eyes of 138 patients with cataract and PEX. All patients with cataract and PEX were divided into three study groups: Group I with normal IOP before surgery; Group II with borderline IOP before surgery (IOP 22–27 mm Hg), Group III was comprised of patients with primary open angle glaucoma treated solely with anti-hypertensive drugs. Patients were followed up for 6 months. Results. Six months after cataract surgery the most pronounced hypotensive effect was observed in Group II and averaged 8.95 mm Hg (39.85 %) (p
Keywords: phacoemulsification; intraocular pressure; pseudoexfoliation syndrome